PENGARUH MEMBACA LIMA BELAS MENIT TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA - Nur Ikhsan, Novio; Cinda Hendrianan, Evinna; Yanti, Lili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to investigate the influence of fifteen minutes of reading on the reading comprehension ability of fifth-grade students at SDN 84 Singkawang. This is a quantitative research using a Quasi-Experimental Design with a Nonequivalent Control Group design. The sample consisted of 26 fifth-grade students. The population was all fifth-grade students at SDN 84 Singkawang. Data collection techniques used a reading comprehension test. Data analysis techniques used quantitative analysis with statistics. The results of the study are: 1) Fifteen minutes of reading made a difference in reading comprehension ability between the experimental and control classes of fifth-grade students, as evidenced by the t-test, where the calculated t-value (16.50) was greater than the t-table value (2.01), meaning the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. 2) Fifteen minutes of reading had a significant impact on students' reading comprehension ability, as evidenced by an effect size (ES) of 3.67, which is categorized as high. This indicates that students' reading comprehension improved when fifteen minutes of reading was implemented. In conclusion, the research showed that implementing fifteen minutes of reading can improve the reading comprehension ability of fifth-grade students at SDN 84 Singkawang.